1994
DOI: 10.1080/00140139408964940
|View full text |Cite
|
Sign up to set email alerts
|

Musculoskeletal disorders among visual display terminal users in a telecommunications company

Abstract: The relationship between workplace factors and work-related upper extremity musculoskeletal disorders (UE disorders) was assessed in a cross-sectional study of 533 telecommunication employees utilizing video display terminals (VDTs). Cases of UE disorders were defined using symptom questionnaires and physical examinations. Data on demographics, individual factors (medical conditions and recreational activities), work organization and practices, and psychosocial aspects of work, including electronic performance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
177
2
8

Year Published

1994
1994
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 291 publications
(197 citation statements)
references
References 35 publications
10
177
2
8
Order By: Relevance
“…The association with exposure to short intervals between calls (less than four seconds), which may be interpreted as an indicator of high work pace, also appears consistent with other reports of elbow-hand/wrist disorders 5,27) . Job insecurity has been reported to increase the risk of musculoskeletal symptoms in the upper limb in both office and industrial workers 9,28) . The mechanism linking job insecurity to musculoskeletal symptoms is not known, but it has been hypothesized that workers who are insecure about their job are more likely to continue working after symptoms development, because of the fear of being fired, without trying to reduce their exposure through a job change, and would be therefore more likely to develop more severe symptoms or disorders 28) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The association with exposure to short intervals between calls (less than four seconds), which may be interpreted as an indicator of high work pace, also appears consistent with other reports of elbow-hand/wrist disorders 5,27) . Job insecurity has been reported to increase the risk of musculoskeletal symptoms in the upper limb in both office and industrial workers 9,28) . The mechanism linking job insecurity to musculoskeletal symptoms is not known, but it has been hypothesized that workers who are insecure about their job are more likely to continue working after symptoms development, because of the fear of being fired, without trying to reduce their exposure through a job change, and would be therefore more likely to develop more severe symptoms or disorders 28) .…”
Section: Discussionmentioning
confidence: 99%
“…A few epidemiological studies of CC workers have investigated the risk of UE symptoms or disorders in relation to workplace characteristics. In general, they observed associations with poor ergonomics of the workstation, high workload or work pace, and adverse psychosocial factors, such as low control, high job strain and poor support from management 3,5,[9][10][11] . However, the comparability of their findings appears limited because of differences in the criteria adopted for case identification, in the risk factors examined and in the analytical methods employed.…”
mentioning
confidence: 99%
“…Nerve entrapment was reported in 4% of subjects. 27 Non-white race, thyroid disease, use of bifocal glasses, and psychosocial variables (like fear of being replaced, work pressure, work-lacking decision-making opportunities) were the other associated factors in upper extremity musculoskeletal disorders among VDT users. Prolonged period of sitting, uncomfortable postures, and mouse use have been linked to musculoskeletal symptoms.…”
Section: Musculoskeletal Symptomsmentioning
confidence: 97%
“…Numerous studies linked musculoskeletal problems among VDT users with workplace demands [5,9]. Hales et al reported that the overall prevalence of potential upper extremity workrelated MSDs defined with a questionnaire and physical examination only at 22% among VDT users in a large telecommunications company [5].…”
Section: Discussionmentioning
confidence: 99%
“…Among these work-related MSDs, tendon-related disorders were most common, followed by muscle-related disorders, nerve entrapment, jointrelated problems and ganglion cysts. Hand-wrist was the area most affected, followed by the neck, the elbow and the shoulder areas [5].…”
Section: Introductionmentioning
confidence: 99%